An analysis of scientific productivity of University of Mysore covered by Web of Science - Kousar, Arshiya (IJRDO- Journal of Educational Research, 2016)
This study has been done to probe scientific productivity of faculty of Mysore University. It helpsto monitor the pattern of research. This paper examines the articles covered in web of sciencefor authorship pattern, degree of collaboration and department wise distribution of papers.This study also provides an overview of knowledge dissemination in various forms